Addressing alcohol use among blood pressure patients in Thai primary care: Lessons from a survey-based stakeholder consultation - Julia M. Lemp; Supa Pengpid; Doungjai Buntup; Till W. Bärnighausen; Pascal Geldsetzer; Karl Peltzer; Jürgen Rehm; Bundit Sornpaisarn; Charlotte Probst (Preventive Medicine Reports, 2022)
Alcohol use is a major risk factor for noncommunicable diseases in Thailand, and one of its pathways is high blood pressure. Given that brief intervention can effectively reduce hazardous alcohol consumption, this study aimed to investigate how hypertensive patients with concomitant alcohol use are identified and treated in Thai primary care settings and what this may mean for screening and lifestyle intervention strategies. In a cross-sectional, mixed-method design, we surveyed 91 participants from three different groups of Thai stakeholders: policy- and decisionmakers; healthcare practitioners; and patients diagnosed with hypertension. Data was collected between December 2020 and May 2021. Responses were analyzed descriptively and using open coding tools to identify current practices, barriers, facilitators, and implications for interventions. All stakeholder groups regarded alcohol use as an important driver of hypertension. While lifestyle interventions among hypertensive patients were perceived as beneficial, current lifestyle support was limited. Barriers included limited resources in primary healthcare facilities, lack of continuous monitoring or follow-up, missing tools or procedures for risk assessment and lifestyle intervention, and stigmatization of alcohol use. Our results suggest that although screening for lifestyle risk factors (including alcohol use) and lifestyle interventions are not yet sufficiently established, a wide range of stakeholders still recognize the potential of interventions targeted at hazardous alcohol use among hypertensive patients. Future interventions may establish standardized assessment tools, be tailored to high-risk groups, and include electronic or remote elements.